Impact of the CARICOM CET reduction on OECS manufacturing and agro-processing - Gonzales, Anthony ([s.n.] [S.l.], 1995)
Reviews the protective arrangements for manufacturing and agro-processing. Identifies several border and inside-the-border measures e.g. tariffs, quantitative restrictions and conditional duty exemptions. Identifies several critical areas of weakness which vary according to the product and sector e.g. high utility charges, high freight costs, high raw material costs and dumping. Posits that reducing the CET in the present climate would not have any efficiency impact and a more prudent strategy should be followed.